2018
DOI: 10.3847/1538-4357/aaad0a
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Substellar Continent on the Climate of a Tidally Locked Exoplanet

Abstract: Previous studies have demonstrated that continental carbon-silicate weathering is important to the continued habitability of a terrestrial planet. Despite this, few studies have considered the influence of land on the climate of a tidally-locked planet. In this work we use the Met Office Unified Model, coupled to a land surface model, to investigate the climate effects of a continent located at the sub-stellar point. We choose to use the orbital and planetary parameters of Proxima Centauri B as a template, to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 67 publications
(121 reference statements)
2
80
1
Order By: Relevance
“…The extent of this ozone removal is driven by the magnitude, frequency, and duration of the stellar activity. We find the planetary surface is potentially habitable in our calculations, in agreement with Boutle et al (2017), with a significant surface area with temperatures above 273 K. We did not consider ice-albedo feedback, following Shields et al (2013); Boutle et al (2017); Lewis et al (2018) who showed this effect is small for M dwarf planets. For our planetary calculations we adopted Earth-like CO 2 concentrations, but we acknowlege they are likely too low if there exists a carbonate-silicate negative feedback cycle (Walker et al 1981).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 69%
See 2 more Smart Citations
“…The extent of this ozone removal is driven by the magnitude, frequency, and duration of the stellar activity. We find the planetary surface is potentially habitable in our calculations, in agreement with Boutle et al (2017), with a significant surface area with temperatures above 273 K. We did not consider ice-albedo feedback, following Shields et al (2013); Boutle et al (2017); Lewis et al (2018) who showed this effect is small for M dwarf planets. For our planetary calculations we adopted Earth-like CO 2 concentrations, but we acknowlege they are likely too low if there exists a carbonate-silicate negative feedback cycle (Walker et al 1981).…”
Section: Discussion and Concluding Remarkssupporting
confidence: 69%
“…The UM has been used previously to study the atmospheric physics of terrestrial exoplanets and hot Jupiters (e.g. Mayne et al (2014a,b); Boutle et al 2017; Lewis et al (2018); Drummond et al (2018)). We couple this model with the Chapman mechanism (Chapman 1930) that describes ozone chemistry in Earth's stratosphere with the hydrogen oxide catalytic cycle.…”
Section: Take Down Policymentioning
confidence: 99%
See 1 more Smart Citation
“…The main focus of the theoretical modeling of exoplanets has been either the well observed hot Jupiter objects, or potentially habitable terrestrial planets. For terrestrial planets 3D General Circulation Models (GCMs) adapted from those used to study Earth, have been applied to explore the potential climates of, for example, Proxima Centauri b (Turbet et al 2016;Boutle et al 2017), the response of an Earth-like climate to weakened and intensified stellar irradiation (Leconte et al 2013;Charnay et al 2013, respectively), alongside studies including surface effects (Lewis et al 2018) and a dynamical ocean (e.g., Wolf et al 2017;Del Genio et al 2017). For hot Jupiters, gas-phase chemical equilibrium simulations have been performed, in 3D using GCMs, across a range of targets (e.g., Kataria et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For all scenarios, we assumed that the planet is tidally locked. Tidal locking can have a profound effect on the climate circulation (Kite et al 2011;Wordsworth 2015;Koll & Abbot 2016;Carone et al 2018;Lewis et al 2018), and likely occurs on shorter timescales and for longer-period planets than previously determined (Barnes 2017). Given the relatively short tidal locking timescale for shortperiod planets, the assumption of tidal locking is sufficiently justified.…”
Section: Climate Modeling and Surface Temperaturementioning
confidence: 91%